Perceived transformational leadership from the coach and athletes’ subjective well-being: A moderated mediated model - Liu, Wenhao; Wang, Wenzhuang; Yang, Shangjian (Frontiers in Psychology, 2023)
Based on human motivation theory and self-determination theory, this study investigated the impact of coaches’ transformational leadership on athletes’ well-being, and the influences of gender and athletes’ basic psychological needs. The survey objects comprised of 432 athletes participating in the Hebei Games in China. The results showed that coaches’ transformational leadership could significantly and positively predict athletes’ well-being. Basic psychological needs had a mediating effect on the relationship between coaches’ transformational leadership and athletes’ well-being. Gender significantly moderated the effect between athletes’ basic psychological needs satisfaction and subjective well-being. Compared with male athletes, female athletes had their basic psychological needs met, and the improvement in their well-being was more significant than the males. Coaches should adapt their transformational leadership to directly improve athletes’ well-being and indirectly achieve their well-being by satisfying the athletes’ basic psychological needs.